ปัจจัยทำนายพฤติกรรมการป้องกันโรคข้อเข่าเสื่อมของพนักงานหญิงนวดแผนไทย - ชนาภา อุดมเวช (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
The objectives of this descriptive predictive research were to study knee osteoarthritis preventive behavior and identify its predictive factors among the female Thai massage practitioners. A simple random sample of 190 female Thai massage practitioners were recruited from Health massage establishments in Bangkok which were certified by the Health Establishment from Department of Health Service Support Ministry of Public Health. Data were collected using 7 questionnaires; 1) demographic data form, 2) knowledge about knee osteoarthritis disease, 3) self-efficacy, 4) attitude, 5) social support, 6) policy of establishments, and 7) knee osteoarthritis preventive behavior questionnaires. All questionnaires were validated by 5 experts. Their CVI were .87, .90, .91, 1.0, .72 and .83, respectively. Their Cronbach’s alpha coefficients were .89, .87, .85, .86 and .88, respectively. Knowledge about knee osteoarthritis disease had KR-20 at .72. Data were analyzed using stepwise multiple regression. The finding revealed that 1) knee osteoarthritis preventive behavior of female Thai massage practitioners was at average level ( x = 22.77, S.D = 3.312) 2) three variables were significant predictors of knee osteoarthritis preventive behavior. They were social support (Beta = .333), policy of establishments (Beta = .309), and knowledge about knee osteoarthritis disease (Beta = .197). They could explain 34.3 % of the variance in knee osteoarthritis preventive behavior of female Thai massage practitioners (p <.05). However, self-efficacy and attitude toward knee osteoarthritis preventive behavior were not able to predict preventive behaviors for female Thai massage practitioners.